Business Performance Analysis And Valuation: Accounting Treatment Implications In Indonesia's Carbon Credit Industry - Larasati, Intan (International Journal of Science, Technology & Management, 2026)
This study examines how accounting treatment choices for special funding schemes affect financial performance and valuation in Indonesia's emerging carbon credit industry. Using PT. Argustara Pilar Utama as a case study, a forestry-based carbon credit company operating under a unique funding arrangement where a single investor fully finances project operations in exchange for fixed-price carbon credit offtake, the research employs quantitative financial analysis methodology including ratio analysis and Discounted Cash Flow (DCF) valuation. Two accounting scenarios are evaluated: Scenario A recognizing investor funds as revenue under IFRS 15, and Scenario B recognizing funds as equity under IAS 32. The findings reveal substantial financial implications from accounting treatment choice. Scenario A produces cumulative positive EBIT of IDR 129.37 billion (2025-2034), Interest Coverage Ratio of 11.37x qualifying for Aa2/AA credit rating, and Enterprise Value of IDR 116.28 billion with WACC of 8.49%. Conversely, Scenario B generates cumulative negative EBIT of IDR 95.60 billion, negative Interest Coverage Ratio triggering D2/D distressed rating, and negative Enterprise Value of IDR 43.99 billion with elevated WACC of 22.81%. The equity value differential between scenarios reaches IDR 160.27 billion. This study concludes that revenue recognition under IFRS 15 is the superior treatment, as net shareholder value of IDR 75.32 billion after tax significantly exceeds zero value under equity recognition, while recommending complementary tax optimization strategies to mitigate double taxation exposure.